Who drives the digital revolution in agriculture? A review of supply‐side trends, players and challenges. Issue 4 (15th March 2021) - Birner, Regina; Daum, Thomas; Pray, Carl
Abstract: Digital agriculture offers far‐reaching opportunities for accelerating agricultural transformation. Based on empirical evidence and guided by economic theory, this study shows that digital agriculture is driven by private firms, including established input firms and global software firms and start‐ups that are new to agriculture. Although there are concerns that digital agriculture will enhance the market power of large agribusiness enterprises and increase the digital divide, a combination of new actors and public action can help accelerate the supply of digital agricultural technology, manage threats of market concentration, and harness the opportunities of digital agriculture for all. Abstract : Related Content: Digital Transformation of the Agricultural Sector: Pathways, Drivers and Policy Implications Related Content: Can digital technologies reshape rural microfinance? Implications for savings, credit, & insurance Related Content: E-commerce's fast-tracking diffusion and adaptation in developing countries